Analysis of serum proteome from type 2 mellitus patient - Minh Phuong, Nguyen Thi; Dan, Pham Duc; Bich Nhi, Nguyen; Chi, Phan Van (Academia Journal of Biology, 2012)
Serum is an exceptional and special proteome in many respects. It contains a lot of essential information for the study and disease diagnosis. However, the analysis of serum is analytically challenging due to the high dynamic concentration range of constituent protein species. Therefore, the fractionation of serum proteome is very necessary. In this study, a combination of different methods: depletion by Aurum Serum Protein MiniKit, thermostable fraction, affinity chromatography, was used to separate proteins from type 2 diabetes mellitus (T2DM) serum. The protein fractions were then digested by trypsin and analyzed by 2DnanoESI-LC-MS/MS. The proteins were named, classified and used to built database by using bioinformatics tools including ID mapping, Swiss-Prot.... It was shown that 468 glycoproteins, 1110 proteins in thermostable fraction, and totally 4044 proteins from 30 T2DM serum samples were identified. Moreover, 26 proteins were found positively associated with T2DM.